Dinamika Collaborative Governance Pada Pencegahan Penyalahgunaan Narkotika Di Kabupaten Aceh Utara - Muslem, Muslem; Mujiburrahman, Mujiburrahman; Nazaruddin, Nazaruddin; Muryali, Muryali; Kardiati, Depita; Isma, Yuli Santri (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
This study investigates the implementation of Aceh Qanun Number 8 of 2018 concerning the facilitation of narcotics abuse prevention in North Aceh, with a specific focus on collaborative governance among the local government, BNNK Lhokseumawe, and the North Aceh Police. North Aceh has experienced increasing narcotics-related threats, yet institutional collaboration in addressing this issue remains underdeveloped. The aim of this study is to analyze the dynamics and constraints of inter-agency collaboration in the implementation of local anti-narcotics policy. Employing a qualitative research design, data were collected through in-depth interviews, direct observation, and documentation analysis involving local stakeholders including public officials, law enforcement, and community representatives. The findings reveal that collaborative efforts are still limited and fragmented due to several factors: weak coordination mechanisms, lack of shared commitment, limited human and financial resources, and misaligned institutional priorities. Moreover, community involvement in prevention programs is minimal, despite its importance as outlined in the policy. These limitations hinder the full realization of Qanun Aceh Number 8 Year 2018. The study emphasizes the need to establish formal and binding coordination structures such as Memoranda of Understanding (MoUs), enhance institutional capacity, and promote inclusive community-based approaches. Strengthening inter-agency synergy and public participation is essential for effective policy outcomes. This study contributes to the broader discourse on collaborative governance in drug prevention and offers insights for designing more integrative and context-specific public policies at the local level.